Self-esteem in crisis: Psychosocial adaptation and masculine identity among Chinese men with azoospermia - Fangliang Zou; Jue Li; Yi Fang; Jiliang Huang; Zikai Feng; Hang Shi; Yu Lan; Yang Zhang; Ruiyun Chen; Yanshan Lin (PLoS ONE, 2026)
Background Azoospermia affects 1% of men and 10–20% of infertile males, yet the psychosocial mechanisms underlying self-esteem impairment remain poorly characterized. Guided by Connell’s Masculinity Theory and Bury’s Biographical Disruption Framework, this mixed methods study examined self-esteem experiences among Chinese men with azoospermia. Methods An explanatory sequential design was employed. Phase 1 surveyed 216 men using Rosenberg’s Self-Esteem Scale, with multiple regression identifying predictors. Phase 2 involved semi-structured interviews with 16 purposively sampled participants, analyzed through thematic analysis. Integration of quantitative and qualitative findings provided comprehensive interpretation. Results Quantitative analysis revealed moderate self-esteem overall (mean = 30.18 ± 3.99), with 10.19% exhibiting low self-esteem. Significant predictors included monthly income ( β = 0.210, p < 0.001), family harmony ( β = 0.141, p = 0.028), and attitudes toward childbearing discussions ( β = 0.159, p = 0.014). Qualitative findings identified five themes, including economic burden, family dynamics, social stigma, treatment uncertainty, and cumulative psychological impacts. Integration demonstrated financial capacity’s dual role as both practical enabler and symbolic compensation for perceived masculine failure. Conclusions Self-esteem in azoospermic men is shaped by interconnected economic, familial, and social factors. Clinical interventions should integrate financial counseling, family-based emotional support, and culturally tailored stigma reduction, highlighting the value of mixed methods in understanding male infertility psychosocial dimensions.